Infographics and Memes on Social Media: New Practice to Disseminate Islamic History Knowledge in the Digital Age - Nawawi, Taosyekh; Sumiati, Wina (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
Knowledge of Islamic history has begun to decrease in demand, especially for the younger generation of Islam in Indonesia. For this reason, a change in the dissemination of information must be more relevant to the times and in demand by the younger generation. Barisan Ummat Neo (BUMN) is a community on social media on Facebook and Instagram that is working progressively to disseminate Islamic history. The focus of the discussion is 1) The root of infographics and memes from their emergence to the development of learning Islamic History on social media, and 2) The role of BUMN in excitingly disseminating Islamic history using infographics and memes. The authors use a qualitative approach by collecting the sources from several interviewees of BUMN and obtaining several primary sources digitally, such as history infographics and memes. This research concludes that the way to learn Islamic history has changed to be more impressive in the digital age using infographics and memes. This dynamic happened because of the contribution of social media fan-page like BUMN, which has an impact on disseminating Islamic history regularly on social media and responded more positively by the young generation.